Adaptation of Executive Functions Rating Scale in Preschool Children - Hermahayu, Hermahayu; Faizah, Rayinda (Universitas Muhammadiyah Metro, 2022)
This study aims to develop measurement instruments for executive functions (EF) in preschool children based on behavioral observation using a rating scale to identify the level of EF ability in children from an early age. Floating EF measurement instruments are adapted and modified by the existing scale, namely the 2nd edition Behavioral Rating Inventory of Executive Functions (BRIEF) prepared by Gioia, Isquith, Guy, and Kenworthy (2015). This study was designed using a research development method consisting of several stages: translation, synthesis, back translations, expert committee review, and pretesting (Beaton et al., 2000). The results of this study indicate that in 60 items of the eight components in the Indonesian version of the executive functions rating scale, 56 items have a high total item correlation index, and four items have a low total item correlation. The reliability value of the scale is 0.965, which indicates that the Indonesian version of the executive functions rating scale is reliable for use.